Managing Resource Rents : The Special Challenges in Postconflict Countries - Bacon, Robert; Tordo, Silvana (World Bank, Washington, DC, 2012)
Resource flows from extractive industries can be a lifeline for postconflict countries, helping to fund critical reconstruction needs. But these resources present issues not found elsewhere in the economy and need to be well managed. Sector governance principles that apply to oil-producing countries in general are even more important in postconflict countries. This note discusses these principles and shows how they apply in two cases, Timor-Leste and Sudan.